THE CORRELATION BETWEEN KNOWLEDGE OF SEXUAL REPRODUCTION, OPENNESS IN DISCUSSING SEXUAL TOPICS, AND AWARENESS OF THE HUMAN PAPILLOMAVIRUS INFECTION TOWARDS WILLINGNESS FOR HUMAN PAPILLOMAVIRUS INFECTION VACCINATION - Dewi Anggraini, Elysia; Manalu, S. Rouli; Qurrota Ayun, Primada (Interaksi Online, 2024)
HPV is the cause of cervical cancer, which is a concern to Indonesian women. Despite various efforts, awareness of the HPV is still low. The government has started a program of free HPV vaccination for primary school to reduce future rates of cancer. However, cultural taboos on sexual discussion hinder the effective reproductive health awareness. This research determines the correlation between knowledge of sexual reproduction, openness in discussing sexual topics, and awareness of the HPV infection towards the willingness for HPV vaccination. This research used purposive sampling with 300 respondents. The sample criteria were women aged 17-24 years and who had not received the HPV vaccination. The hypotheses testing was conducted with Kendall’s W and Chi-Square using SPSS. The results showed that the correlation between knowledge of sexual reproduction and awareness of the HPV infection towards openness in discussing sexual topics with Sig. value of 0.006 < 0.01, stated as very significant from the Kendall’s W. Additionally, the correlation between openness in discussing sexual topics towards willingness for HPV infection vaccination with Sig. value of 0.000 < 0.01, stated as very significant from the ChiSquare. The findings of this study support the validity of the KAP model.